Tinjauan Yuridis Ketentuan Uang Muka di Bawah Ketentuan Peraturan Menteri Keuangan dan Otoritas Jasa Keuangan - Ardrian Yolanda; Ali Hanafiyah (JOURNAL of LEGAL RESEARCH, 2020)
The goal of this analysis is to decide the implementation of the down payments in the provisions of the relevant laws and regulations and how the legal implications of the violation of the provisions laid down in Regulation No 43/PMK.010/2012 of the Minister of Finance concerning the advances for customer financing of motor vehicles in financing companies are to be decided. , and Financial Services Authority Regulation Number 35 / POJK.05 / 2018 concerning Business Conduct of Financing Companies. The method of research used in this research is legal normative, i.e. legal research carried out by analyzing library resources or secondary data as fundamental research material by undertaking a review of the laws and literature pertaining to the problem under review. The findings of this analysis show that Regulation No 43 / PMK.010 / 2012 of the Minister of Finance concerning Developments for Automotive Financing for Motor Vehicles in Financing Companies and Regulation No 35 / POJK.05 / 2018 of the Financial Services Authority concerning Market Activity of Financing Companies do not interfere with the existing Regulation. However, this regulation cannot be implemented optimally in the field, because there are still many violations regarding the existence of low Down Payment (DP) promotions at dealers who have collaborated with leasing. However, because there is no strict supervision in the field, dealers / leasingers often commit violations, which creates uncertainty in law enforcement.